2006
DOI: 10.1038/sj.cgt.7700919
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral vector-mediated RTVP-1 gene-modified tumor cell-based vaccine suppresses the development of experimental prostate cancer

Abstract: We previously identified a novel p53 target gene, RTVP-1, that possesses unique cytotoxic and immunostimulatory activities which make it potentially useful for cancer gene therapy. To test the therapeutic potential of RTVP-1 in a gene-modified tumor cell-based vaccine model, we used an adenoviral vector capable of efficient transduction and expression of RTVP-1 (AdRTVP-1), together with a highly metastatic mouse prostate cancer cell line (178-2 BMA). A vaccine was prepared with 178-2 BMA cells transduced with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…A tumor suppressor function for GLIPR1 is also supported by previous studies of the effects of GLIPR1 overexpression both in vitro and in vivo (4)(5)(6)(7)17); however, direct genetic evidence of such function was lacking until this study. We now show that Figure 4.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A tumor suppressor function for GLIPR1 is also supported by previous studies of the effects of GLIPR1 overexpression both in vitro and in vivo (4)(5)(6)(7)17); however, direct genetic evidence of such function was lacking until this study. We now show that Figure 4.…”
Section: Discussionsupporting
confidence: 60%
“…Functional analysis revealed that overexpression of either Glipr1 or GLIPR1 induces apoptosis and suppresses colony formation in vitro in various mouse and human cancer cell lines, independently of p53 status (4,5). Adenoviral vector-mediated delivery of Glipr1 into orthotopic mouse prostate cancer significantly suppressed tumor growth and metastasis to lung (6), whereas administration of a novel Glipr1 gene modified tumor cell vaccine to mice had significant antitumor activity in a preclinical model of recurrent prostate cancer (7). Adenoviral vectormediated GLIPR1 gene therapy is currently in a phase I/phase II clinical trial (IND13033), and GLIPR1 protein therapy is in preclinical development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to increased rates of apoptosis, decreased tumor progression after virally mediated delivery in vivo appeared to depend, at least in part, on antiangiogenic and immunostimulatory activities (259). The preimmunization of mice with a Glipr1-modified tumor cell vaccine was also partially protective against the development of prostate cancer in an orthotopic cancer model (260), and, perhaps most compellingly, mice lacking Glipr1 had a significantly increased predisposition to spontaneous tumor growth when compared with wild-type littermates (261). It is also of note that Glipr heterozygous animals were significantly more disposed to developing tumors than wild-type animals, suggesting that the proapoptotic effect of GLIPR1 is stochastic in nature (261).…”
Section: Cap Proteins In Cancermentioning
confidence: 90%
“…It has been suggested that GLIPR1 plays a role in the immune surveillance (Szyperski et al 1998). Adenoviral vector-mediated delivery of mouse GLIPR1 into orthotopic mouse prostate cancer signiWcantly suppressed tumor growth and metastasis to lung (Satoh et al 2003), whereas administration of a mouse GLIPR1 gene modiWed tumor cell vaccine to mice had signiWcant antitumor activity in a pre-clinical model of recurrent prostate cancer (Naruishi et al 2006). These properties suggest that GLIPR1 is a tumor suppressor gene in prostate cancer and possibly in other malignancies.…”
Section: Introductionmentioning
confidence: 97%